Leonardo's lost princess : one man's quest to authenticate an unknown portrait by Leonardo da Vinci - Silverman, Peter (Wiley, 2012)
"How an oddly attributed $19,000 picture proved to be a $100 million work by Leonardo da Vinci-a true art-world detective storyIn late 2010, art collector Peter Silverman revealed that a "German, early 19th century" portrait he had bought for $19,000 was, in fact, a previously unknown drawing by Leonardo da Vinci-an exquisite depiction of Bianca Sforza, rendered 500 years ago. In Leonardo's Lost Princess, Silverman gives a riveting first person account of how his initial suspicions of the portrait's provenance were confirmed repeatedly by scientists and art experts. He describes the path to authentication, fraught with opposition and controversy. The twists and turns of this fascinating, decade-long quest lead from art history to cutting-edge science, and from a New York art gallery to Paris, Milan, Zurich, and finally a Warsaw library where the final, convincing evidence that the portrait was indeed by Da Vinci was found. Takes an up-close look at the workings of the art world and at figures ranging from dealers and connoisseurs to a suspected forger Discusses current scientific techniques used to investigate and authenticate works of art, such as carbon dating and cutting-edge photography Uses Silverman's drawing as an entree into Leonardo da Vinci's world: his studio, his style, and his methods Explores the intersection of art and science in the authentication process, involving the work of a man who embodied that intersection Unearthing the secrets of a work that were almost lost to history, the book is ideal reading for art lovers and anyone interested in an astounding case of "whodunnit""--Provided by publisher